Experiences and perceptions of nursing staff working with long-stay patients in a high secure psychiatric hospital setting - Dutta, Snigdha; Majid, Shazmin; Völlm, Birgit (Lippincott Williams & Wilkins, 2016)
Background and Objective: Forensic psychiatric nursing is a demanding nursing specialty that deals with a highly complex group of patients who are detained in restrictive environments, often for lengthy periods. There is little information about the daily experiences of these nurses. This study sought to explore the roles and relationships of forensic psychiatric nurses with long-stay patients in a high secure hospital in England.